Anchor test and long-term monitoring of grouted anchors instrumented with Fiber Bragg Grating sensing technology - Daniela Runcziková; Jan Záleský; Marek Záleský; Jakub Koller; Ladislav Šašek (Acta Polytechnica)
Geotechnical monitoring of anchors provides fundamental data for analysis and evaluation to ensure safe environment. The use of optic fiber sensing technology, especially Fiber Bragg Gratings, brings many advantages of optic fiber sensors, such as high measurement accuracy, real-time continual monitoring of deformation, on-line access to data and resistance against electromagnetic interferences. This article deals with anchor tests instrumented with FBG deformation gauges of the root and the tendon of the pre-stressed strand anchor in a test field in the Central Bohemian Region. First, the anchor with three optic cables with FBG sensors for measurement of axial deformation was subjected to six loading stages of the anchor test. Most of the sensors measured values of axial deformation less than 200 με and the root mobilisation was observed. Then, the measurement continued by 26-day long-term monitoring and a trend of a small increase of deformations occurred.